PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA TERPADU TIPE WEBBED BERBASIS INKUIRI TERBIMBING UNTUK MELATIH KEMANDIRIAN BELAJAR DAN KECAKAPAN HIDUP SISWA SMP - Syamsudin Syamsudin; Muslimin Ibrahim; Wahono Widodo (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
Research has been done to develop the kind of integrated science teaching type webbed (Syllabus, Lesson Plans, Student Work Sheet, Student Book, Student Achievement Test) with guided inquiry model that aims to teach self directed learning and life skills junior high school students. Learning materials developed by four D model there are define, design, develop, and disseminate. Learning materials were validated by the experts to determine the validity of the materials and tested on 35 students of grade VII junior high school odd semester academic year 2015/2016 using the One Group Pre-test and Post Test Design. The data were analyzed by descriptive quantitative-qualitative. The results are: 1) The validity of the materials is very valid category (score 3.63); 2) Readability worksheet shows 100% the content interesting and easy to understand, 82.86% Student Work Sheet attractive appearance and legibility Student Book legible and suitable for use in junior high school students with an average number of sample sentences readings taken by researchers is 5.93 sentence in 100 words with the average number of syllables 145.2; 3) the successful is very good (average score of 3.71); 4) The students responded very positively (97.14%); 5) Students activities are student centered type; 6) increased student learning achievement (N-gain 0.74); 7) The self directed learning and improve students' life skills. The conclusions of this research are integrated science teaching materials types based guided inquiry type webbed developed is feasible to use in teaching self directed learning and ability of life skills junior high school students. Telah dilakukan penelitian pengembangan perangkat pembelajaran IPA terpadu tipe webbed (Silabus, RPP, LKS, Buku Siswa, Tes Hasil Belajar) dengan model inkuiri terbimbing yang bertujuan untuk melatih kemandirian belajar dan kecakapan hidup siswa SMP. Perangkat pembelajaran dikembangkan menggunakan model 4D (four D model) terdiri dari tahap pendefinisian (define), perancangan (design), pengembangan (develop) dan penyebaran (disseminate). Perangkat pembelajaran divalidasi oleh para pakar untuk mengetahui validitas perangkat dan diujicoba pada 35 siswa kelas VII SMP semester gasal tahun ajaran 2015/2016 dengan rancangan One-Group Pre test and Post test Design. Analisis data dilakukan secara deskriptif kuantitatif-kualitatif dengan hasil: 1) Validitas perangkat kategori sangat valid (skor 3.63); 2) Keterbacaan LKS menunjukkan 100% isi LKS menarik dan mudah dipahami, 82.86% penampilan LKS menarik dan keterbacaan Buku Siswa terbaca dan layak digunakan untuk siswa SMP dengan rata-rata jumlah kalimat sampel bacaan yang diambil peneliti adalah 5,93 kalimat dalam 100 kata dengan rata-rata jumlah suku kata 145,2; 3) Keterlaksanaan sangat baik (skor rata-rata 3.71); 4) siswa merespon sangat positif (97.14%); 5) Aktivitas siswa bersifat student center; 6) Hasil belajar siswa meningkat (N-gain 0.74); 7) Kemandirian belajar dan kecakapan hidup siswa meningkat. Simpulan penelitian ini adalah perangkat pembelajaran IPA terpadu tipe webbed berbasis inkuiri terbimbing yang dikembangkan sudah valid, praktis, dan efektif untuk melatihkan kemandirian belajar dan kemampuan kecakapan hidup siswa SMP.